2018
DOI: 10.1007/s11357-018-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors that positively or negatively mediate the effects of age on working memory across the adult life span

Abstract: Working memory abilities significantly decrease with advancing age; hence, the search for factors that may increase or mitigate this decline is critical. Several factors have been identified that influence working memory; however, their effects have been mainly assessed separately and rarely together with other factors in the same sample. We examined 120 variables to search for factors that jointly act as mediators of working memory decay across the adult life span. A sample of 1652 healthy adults was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Investigation of the molecular background of this type of memory loss as well as the assessment of the effectiveness of different drug candidates is very complicated in rodents. Dementia occurs as a complex syndrome of cognitive, functional, and emotional alterations in humans (Ferrucci et al 2018; Cansino et al 2018); only some symptoms are reproducible in animal models (Mitchell et al 2015; Wahl et al 2017). Furthermore, the mortality, morbidity, and sensitivity to different interventions have much higher risk over 12 months in rodents (Snyder et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the molecular background of this type of memory loss as well as the assessment of the effectiveness of different drug candidates is very complicated in rodents. Dementia occurs as a complex syndrome of cognitive, functional, and emotional alterations in humans (Ferrucci et al 2018; Cansino et al 2018); only some symptoms are reproducible in animal models (Mitchell et al 2015; Wahl et al 2017). Furthermore, the mortality, morbidity, and sensitivity to different interventions have much higher risk over 12 months in rodents (Snyder et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have clearly indicated that aging is the primary risk factor for cognitive decline and neurodegenerative disease ( 1 3 ). Several factors have been implicated in cognitive decline with age, including a decrease in circulating growth factors and neurosteroids and/or an increase in inflammatory cytokines ( 4 ).…”
mentioning
confidence: 99%
“…Moderate alcohol consumption increased high-density lipoprotein cholesterol and diminished the accumulation of platelets (Arranz et al, 2012). In an adult life span sample, it was observed that beer consumption was a positive mediator of the effects of age on verbal working memory (Cansino et al, 2018b). The present outcome goes beyond these previous findings because it not only suggests that beer consumption may be beneficial for memory but also provides evidence that its consumption may be needed to avoid source memory capability loss.…”
Section: Discussionmentioning
confidence: 99%